Search for CP violation in Ξ+c → pK−π+ decays using model-independent techniques - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (The European physical journal. C, Particles and fields, 2020)
A first search for CP violation in the Cabibbo-suppressed Ξ+c→pK−π+ decay is performed using both a binned and an unbinned model-independent technique in the Dalitz plot. The studies are based on a sample of proton-proton collision data, corresponding to an integrated luminosity of 3.0fb−1, and collected by the LHCb experiment at centre-of-mass energies of 7 and 8TeV. The data are consistent with the hypothesis of no CP violation.